SERANGAN KUMBANG AMBROSIA PADA KAYU SUNGKAI (PERONEMA CANESCENS) - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Susceptibility of sungkai wood (Peronema canescens) to ambrosia beetle infestations was studied. Fresh cut sungkai poles, measuring about 20 cm in diameter and 75 cm in length, were selected for the test. Six pole treatments were chosen each of which was represented by five replications. The test poles were kept under shade near felling site. Observations were respectively made for the number of ambrosia beetle tunnels occuring on the pole surface after 3, 6, 9, 15, and 40 days. The development pattern of the beetle gallery system, based on number of tunnel showed up on some peeling off areas of some consecutive depth of the heaviest infested test pole, was also observed.The result shows that unbarked (with and without flint kote) poles are practically unattack by the borer. Poles treated with ethanol (flint-koted barked and unbarked) were not attacked until day 9. The most severe attack occurs on the barked poles (with or without flint kote) Although the attack practically does not seem to occur until day 21. Regression equation Y =27,65 + 6,93X - 5,51X , where Y =number of tunnels found on each peeling area and X = depth of peeling (cm), represents the development pattern of the beetle galleries within the log.